Measuring direct non-medical burden among patients with advanced non-small cell lung cancer in China: is there a difference in health status? - Xia, Yu; Chen, Yingyao; Chen, Jia; Gan, Yuying; Su, Chunxia; Zhang, Haibo; Long, Enwu; Yan, Fei; Yang, Yi (Frontiers in Public Health, 2023)
Objective This study was conducted to estimate the direct non-medical cost of advanced non-small cell lung cancer (NSCLC) patients and explore whether its associated factors vary by health status. Methods Data were obtained from 13 centers in five provinces for patients with advanced NSCLC in China. The direct non-medical cost of patients since the patients were diagnosed with NSCLC included the cost of transportation, accommodation, meal, hired caregiving, and nutrition. We measured patients' health status by EQ-5D-5L instrument and divided them into good (≥0.75) and poor (<0.75) groups based on the utility score. A generalized linear model (GLM) was used to assess independent associations between statistically significant factors and non-medical financial burden in health status subgroups. Results Data from 607 patients were analyzed. The direct non-medical cost associated with advanced NSCLC since diagnosis was 2,951 per case (4,060 in the poor health group and 2,505 in the other), with nutrition costing the most. GLM results showed that residence(Urban area vs. Rural area: −1.038, [−2.056, −0.02]), caregivers' occupation type (Farmer vs. Employee: −1.303, [−2.514, −0.093]), hospitalization frequency (0.077, [0.033, 0.12]), average length of hospital stay (0.101, [0.032, 0.17]), and pathological type (Squamous carcinoma vs. Non-squamous carcinoma: −0.852, [−1.607, −0.097]) were independent factors influencing direct non-medical cost in the poor health group. Among participants with good health status, residence (Urban area vs. Rural area: −0.621, [−1.005, −0.236]), marital status (Others vs. Married: 0.762, [0.035, 1.488]), patients' employment status, current caregiving time per day (more than 9 hours per day vs. less than 3 hours per day: 0.471, [0.134, 0.807]), duration of disease (0.015, [0.007, 0.024]), and hospitalization frequency (0.091, [0.068, 0.113]) were statistically associated factors. Conclusion The direct non-medical economic burden of advanced NSCLC patients in China is considerable and differs by health status. Strengthening accessibility for more effective therapies and early nutritional intervention to improve prognosis, and further promoting accessible care forms within relevant healthcare insurance coverage may be potentially feasible approaches to alleviate the direct non-medical economic burden for patients and their families.